Beam‐reconfigurable crescent array antenna with AMC plane - Herwansyah Lago; Ping, Jack Soh; Mohd Faizal Jamlos; Zahriladha Zakaria (2018)
A beam‐reconfigurable crescent array antenna with AMC plane is presented for application at 9.41 GHz. The unit cell of the AMC plane is modeled based on a square patch integrated with rectangular ring slot with mirrored C‐shaped structures, placed between two layers of Taconic TLY‐5 substrate and located near to the main radiating element. The presented AMC design is achieved an operating bandwidth of 2.82 GHz (30%) with a center frequency of 9.41 GHz. It is found that the AMC plane can reduce the thickness of the structure in comparison to the use of a conventional ground plane, which leads to the overall compactness size of the proposed antenna of 1.1λ × 2.57λ. Moreover, through the implementation of 12 × 4 AMC unit cell, the proposed antenna improved its performance with a maximum gain and total efficiency of 10.5 dB and 97%, respectively. Meanwhile, the antenna reconfigurability is realized by integrating RF MEMS switches on its right and left arm symmetrically. The presence of a T‐shaped Yagi‐Uda‐like parasitic further widened the beam steering angle to ±63° via mutual coupling. The obtained results demonstrate a good agreement between the simulation and measurement and have a huge potential for development of X‐band radar.